A numerical study on the non‐isothermal flow characteristics and hydrate risk of CO2 in buried transmission pipelines under the gas‐phase transportation mode. Issue 1 (13th November 2019) - Liu, Wenyuan; Hu, Jinqiu; Sun, Fengrui; Sun, Zheng; Li, Xiangfang
Abstract: With the development and progress of carbon dioxide (CO2 ) capture and storage technology, the study of the flow assurance of CO2 in transmission pipelines needs to be further deepened. In this study, aiming at the gas‐phase transportation mode of CO2, first, a new prediction model of temperature, pressure as well as hydrate formation risk in buried CO2 transmission pipelines is established. Second, the model solving methods of differential discretization and piecewise iteration are introduced in detail. Third, model validation and sensitivity analysis of typical transmission parameters are performed. The results show that: (a) there is good agreement between the model prediction results and software simulation results. (b) The subcooling and the length of the hydrate formation region increase with the increase in the transmission rate. Appropriate increase in the CO2 transmission rate can reduce the risk of hydrate formation in CO2 transmission pipelines. (c) The subcooling and the length of the hydrate formation region decrease as the transmission temperature increases. In order to prevent hydrate risk in the CO2 transmission process, low transmission temperatures should be avoided. (d) The subcooling and the length of the hydrate‐formation area increase first and then decrease as the transmission pressure increases. Appropriate increase in CO2 transmission pressure is conducive to avoiding hydrate formation risk. This study provides basic theoretical guidance for optimizing transmission parameters and risk assessment of hydrate formation in CO2 transmission pipelines. © 2019 Society of Chemical Industry and John Wiley & Sons, Ltd.